2010
DOI: 10.1001/archophthalmol.2010.166
|View full text |Cite
|
Sign up to set email alerts
|

Mortality After Diagnosis of Small Melanocytic Lesions of the Choroid

Abstract: To evaluate the risk of dying of metastatic choroidal melanoma in patients with small, indeterminate, pigmented lesions of the uveal tract. Methods: A cohort of 1063 consecutive patients were evaluated in the Ocular Oncology Clinic of the Massachusetts Eye and Ear Infirmary between January 1976 and June 1996 with definite choroidal nevus (n = 256), indeterminate lesions (n=334), or small melanoma (n=373). Deaths occurring up to December 1998 were identified through active follow-up or by a search of the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…Five patients (5.1%) died of metastasis after a median follow-up period of 51 months. Lane et al (2010) deaths occurred (median follow-up 8.2 years). Death rates for metastasis at 5, 10, 15 years were 2%, 5% and 7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Five patients (5.1%) died of metastasis after a median follow-up period of 51 months. Lane et al (2010) deaths occurred (median follow-up 8.2 years). Death rates for metastasis at 5, 10, 15 years were 2%, 5% and 7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more recent work has found that, even after controlling for gep, tumour size (that is, basal dimension ≥ 12 mm) is an independent predictor of metastasis at 5 years 19 . In contrast, several small noncomparative case series have suggested that patients with small indeterminate lesions who are carefully selected by an ophthalmologist can be observed for tumour growth before treatment initiation without adversely affecting survival [43][44][45][46][47] . The American Brachytherapy Society guidelines suggest that patients being observed should be counselled about the small (yet still unquantified) increased risk of metastasis with observation 30 .…”
Section: Observationmentioning
confidence: 99%
“…It has been assumed that larger UM are innately more aggressive, as they have either high-risk genetic factors from the outset or have accumulated these factors over time, termed ‘crescendo malignancy’ [ 67 ]. On this basis, it is conventional practice in many ocular oncology centers to monitor small, indeterminate uveal melanocytic tumors for months (or even years) until growth is documented [ 68 , 69 , 70 , 71 , 72 ]. Weis et al demonstrated that most of these indeterminate lesions are low-risk D3-UM [ 73 ].…”
Section: Discussionmentioning
confidence: 99%